Land Management - Altaf, Mir (2012)
The Wenchuan earthquake affected 20 cities, 158 counties, and 3,655 towns and villages. Geographic and demographic conditions varied significantly from small, rural villages to county-level cities, as did the magnitude of the physical damages. The reconstruction strategy and plan, inclusive of land management, depended on the conditions specific to each locale, from in situ reconstruction for the cities and towns with limited damage in relatively safe locations to the possibility of physical relocation from high- to low-risk locations that is, total reconstruction. This land management note focuses in particular on how to efficiently provide land to the Wenchuan earthquake-affected population and more generally on land management issues. It is based on two World Bank works: (i) a study entitled, 'the spatial organization of cities: deliberate outcome or unforeseen consequence?" and (ii) the ongoing Sichuan Urban Development Project, where new urban land in peri-urban areas is being developed through rational spatial development planning.